Residual Quantitative Flow Ratio to Estimate Post‐Percutaneous Coronary Intervention Fractional Flow Reserve. (1st September 2021) - van Diemen, Pepijn A.; de Winter, Ruben W.; Schumacher, Stefan P.; Bom, Michiel J.; Driessen, Roel S.; Everaars, Henk; Jukema, Ruurt A.; Somsen, Yvemarie B.; Popelkova, Lenka; van de Ven, Peter M.; van Rossum, Albert C.; van de Hoef, Tim P.; et al.
Abstract : Objectives . Quantitative flow ratio (QFR) computes fractional flow reserve (FFR) based on invasive coronary angiography (ICA). Residual QFR estimates post‐percutaneous coronary intervention (PCI) FFR. This study sought to assess the relationship of residual QFR with post-PCI FFR. Methods . Residual QFR analysis, using pre-PCI ICA, was attempted in 159 vessels with post-PCI FFR. QFR lesion location was matched with the PCI location to simulate the performed intervention and allow computation of residual QFR. A post-PCI FFR < 0.90 was used to define a suboptimal PCI result. Results . Residual QFR computation was successful in 128 (81%) vessels. Median residual QFR was higher than post-PCI FFR (0.96 Q1–Q3: 0.91–0.99 vs. 0.91 Q1–Q3: 0.86–0.96, p < 0.001 ). A significant correlation and agreement were observed between residual QFR and post-PCI FFR ( R = 0.56 and intraclass correlation coefficient = 0.47, p < 0.001 for both). Following PCI, an FFR < 0.90 was observed in 54 (42%) vessels. Specificity, positive predictive value, sensitivity, and negative predictive value of residual QFR for assessment of the PCI result were 96% (95% confidence interval (CI): 87–99%), 89% (95% CI: 72–96%), 44% (95% CI: 31–59%), and 70% (95% CI: 65–75%), respectively. Residual QFR had an accuracy of 74% (95% CI: 66–82%) and an area under the receiver operating characteristic curve of 0.79 (95% CI: 0.71–0.86). Conclusions . A significant correlation and agreement between residual QFR and post-PCI FFR were observed. Residual QFR ≥ 0.90 did not necessarily commensurate with a satisfactory PCI (post-PCI FFR ≥ 0.90). In contrast, residual QFR exhibited a high specificity for prediction of a suboptimal PCI result.